2021
DOI: 10.3390/pathogens11010003
|View full text |Cite
|
Sign up to set email alerts
|

Cortactin Promotes Effective AGS Cell Scattering by Helicobacter pylori CagA, but Not Cellular Vacuolization and Apoptosis Induced by the Vacuolating Cytotoxin VacA

Abstract: Cortactin is an actin-binding protein and actin-nucleation promoting factor regulating cytoskeletal rearrangements in eukaryotes. Helicobacter pylori is a gastric pathogen that exploits cortactin to its own benefit. During infection of gastric epithelial cells, H. pylori hijacks multiple cellular signaling pathways, leading to the disruption of key cell functions. Two bacterial virulence factors play important roles in this scenario, the vacuolating cytotoxin VacA and the translocated effector protein CagA of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Furthermore, experiments employing cortactin shRNA knockdown and toxin VacA, another prominent virulence factor of H. pylori with known pro-apoptotic properties, indicated a role for cortactin in the intracellular transport of VacA and the apoptotic response (Chang et al, 2016). However, similar experiments using cortactin knockout cells refuted the role of cortactin in both responses (Sharafutdinov et al, 2021b). The precise reasons for these discrepancies will have to be clarified in future studies, but they do underline the importance of experimental approaches alternative to siRNA or shRNA, in which the loss of function of a given protein may not be complete.…”
Section: Helicobacter Pylorimentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, experiments employing cortactin shRNA knockdown and toxin VacA, another prominent virulence factor of H. pylori with known pro-apoptotic properties, indicated a role for cortactin in the intracellular transport of VacA and the apoptotic response (Chang et al, 2016). However, similar experiments using cortactin knockout cells refuted the role of cortactin in both responses (Sharafutdinov et al, 2021b). The precise reasons for these discrepancies will have to be clarified in future studies, but they do underline the importance of experimental approaches alternative to siRNA or shRNA, in which the loss of function of a given protein may not be complete.…”
Section: Helicobacter Pylorimentioning
confidence: 99%
“…The precise balance between cortactin and coronin 1B activities, and their competitive binding to F‐actin and Arp2/3 will definitely impact actin remodeling and cell motility, and will thus be utilized by pathogens as well. In addition, only two of the studies discussed here used a CRISPR‐Cas9 knockout of cortactin (Knorr et al, 2021; Sharafutdinov et al, 2021b). We are convinced that modern genome editing methodology will be very useful in defining the precise roles of cortactin and its interaction partners in infection biology.…”
Section: Outlook and Perspectivesmentioning
confidence: 99%
“…Because of these central cellular properties, cortactin also represents a favorite target of various microbial pathogens by promoting their adhesion, invasion and intracellular trafficking ( Schnoor et al., 2018 ; Weaver, 2008 ). For instance, the gastric pathogen and carcinogen H. pylori can exploit cortactin activity in order to control cell attachment to the extracellular matrix and cell motility using its translocated effector protein CagA ( Sharafutdinov et al., 2022b ; Tegtmeyer et al., 2011 ). In addition, previous studies revealed that ectopically expressed CagA binds Par1b to induce its inactivation and disrupt cell polarity ( Saadat et al., 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the cells were washed with HEPES-buffer and analyzed under a DMI4000B epifluorescence microscope (Leica Microsystems, Wetzlar, Germany). Cells stained positive for either annexin V-FITC or PI were considered as undergoing apoptosis/necrosis and were presented as percentage out of all counted cells as described ( Sharafutdinov et al, 2022 ). Welch's ANOVA combined with Holm-Sidak's post-test was used to define the differences between the groups with p ​≤ ​0.05 (∗) considered to be significant.…”
Section: Methodsmentioning
confidence: 99%